The Solitary Pulmonary Nodule: Is It Benign or Malignant? - Haryati Haryati; Dimas Satrio Baringgo (Indonesian Society of Respirology (ISR), 2023)
Solitary pulmonary nodules (SPN) are round-shaped opacities with or without firm borders and ≤3 cm in diameter. 40% of solitary pulmonary nodules in high-risk populations are malignant and >10 mm in diameter. With the high incidence of pulmonary cancer, diagnosing pulmonary nodules is essential for clinicians. This review aims to discuss more solitary pulmonary nodules based on multiple recommendations for diagnosis and management. Malignancy probability assessment is the first step in evaluating each patient with new pulmonary nodules, as it significantly affects the prognosis of the disease. The assessment depends on the risk factors present in the patient, which are cigarettes, age, history of cancer, and family history. Radiological evaluation is the second phase in pulmonary nodule evaluation. Predictors of malignant nodules that should be assessed are nodule size, growth rate, nodule morphology, location, and enhancement. Many guidelines have been published regarding treating solitary pulmonary nodules, including the Fleischner Society, ACCP, and BTS guidelines.